Proteomic changes in response to crystal formation in Drosophila Malpighian tubules. - Chung, V; Konietzny, R; Charles, P; Kessler, B; Fischer, R; Turney, B (Taylor and Francis, 2016)
Kidney stone disease is a major health burden with a complex and poorly understood pathophysiology. Drosophila Malpighian tubules have been shown to resemble human renal tubules in their physiological function. Herein, we have used Drosophila as a model to study the proteomic response to crystal formation induced by dietary manipulation in Malpighian tubules. Wild-type male flies were reared in parallel groups on standard medium supplemented with lithogenic agents: control, Sodium Oxalate (NaOx) and Ethylene Glycol (EG). Malpighian tubules were dissected after two weeks to visualize crystals with polarized light microscopy. The parallel group was dissected for protein extraction. A new method of Gel Assisted Sample Preparation (GASP) was used for protein extraction. Differentially abundant proteins (p<0.05) were identified by label-free quantitative proteomic analysis in flies fed with NaOx and EG diet compared with control. Their molecular functions were further screened for transmembrane ion transporter, calcium or zinc ion binder. Among these, 11 candidate proteins were shortlisted in NaOx diet and 16 proteins in EG diet. We concluded that GASP is a proteomic sample preparation method that can be applied to individual Drosophila Malpighian tubules. Our results may further increase the understanding of the pathophysiology of human kidney stone disease.